2021
DOI: 10.11606/issn.1678-4456.bjvras.2021.175001
|View full text |Cite
|
Sign up to set email alerts
|

role of prostaglandin F2α on ovulation and LH release in cows

Abstract: This study aimed to evaluate the role of prostaglandin F2α (PGF) on ovulation. In Experiment 1, cows were randomly allocated to two treatments to receive 150 μg of d-Cloprostenol (PGF Group, n = 12) or 2 mL of NaCl 0.9% (Control Group, n = 11) and CIDRs, were removed 4 days later. No cow ovulated in Control and PGF groups. In Experiment 2, cows were randomly separated into two experimental groups to receive 4 injections of 150 μg of d-Cloprostenol (n = 9) or 2 mL of NaCL 0.9% (n = 9). In this experiment, ovul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Investigations in normal beef heifers and cows receiving the 7-day Co-Synch + CIDR protocol [23] have observed that blood flow (vascularised area in pixels) of large POF (14.1-17.5 mm in diameter) tended to be greater than small POF (10.8-12.8 mm in diameter). Moreover, the significant increase in vascularity (vascularised area in percent) in POF (>11.5 mm in diameter) suggested that systemic hormonal stimulation may locally induce the ovulatory process [24]. In the cyclic buffalo model, a previous study applied the total blood supply (vascularised area in pixels) of ovarian follicles for predicting the effective hormonal synchronisation that the total blood flow to the DF was greater in females receiving the CIDR-PGF-based protocol than buffaloes receiving the Ovsynch-CIDR-based protocol at oestrous onset [25].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations in normal beef heifers and cows receiving the 7-day Co-Synch + CIDR protocol [23] have observed that blood flow (vascularised area in pixels) of large POF (14.1-17.5 mm in diameter) tended to be greater than small POF (10.8-12.8 mm in diameter). Moreover, the significant increase in vascularity (vascularised area in percent) in POF (>11.5 mm in diameter) suggested that systemic hormonal stimulation may locally induce the ovulatory process [24]. In the cyclic buffalo model, a previous study applied the total blood supply (vascularised area in pixels) of ovarian follicles for predicting the effective hormonal synchronisation that the total blood flow to the DF was greater in females receiving the CIDR-PGF-based protocol than buffaloes receiving the Ovsynch-CIDR-based protocol at oestrous onset [25].…”
Section: Discussionmentioning
confidence: 99%